2004
DOI: 10.1007/978-3-540-24693-0_6
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Performance of TCP in the Presence of Interacting UDP Flows in Ad Hoc Networks

Abstract: Abstract.In this paper, we study how fairness affects the performance of TCP over ad hoc networks with IEEE 802.11 at the MAC layer. The problem addressed is that the throughput of TCP flows degrades severely in the presence of heavily loaded UDP flows. Our contribution is twofold. First, we identify the factors affecting the TCP throughput by providing a micro-analysis of the performance at a level of detail that is not seen in previous studies. The intuition obtained from the first part leads us to our secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
(37 reference statements)
0
10
0
Order By: Relevance
“…Gupta et al [19] discuss the case where TCP flows are degraded by heavily loaded UDP flows in a static ad hoc network. In this case, the authors showed that increasing the RL value allows improvement of TCP goodput without diminishing UDP flow goodput.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Gupta et al [19] discuss the case where TCP flows are degraded by heavily loaded UDP flows in a static ad hoc network. In this case, the authors showed that increasing the RL value allows improvement of TCP goodput without diminishing UDP flow goodput.…”
Section: Related Workmentioning
confidence: 99%
“…However, as far as we know all the studies concerning TCP performance enhancements [17][18][19] were conducted in static multihop ad hoc environments.…”
Section: Related Workmentioning
confidence: 99%
“…Many MAC protocols have been proposed to improve TCP performance [14]- [16]. The scheme in [17] can detect the degradation of TCP performance in the presence of UDP, which has been considered only in ad hoc networks. Several schemes in [18]- [20] improve the performance by giving more channel access to AP than STAs.…”
Section: Related Workmentioning
confidence: 99%
“…This work has lead to two conferences [Gupta02,Gupta04] and is being submitted to a journal. More details on this project can be found there.…”
Section: Denial Of Service Attacks At the Mac Layer In Manetsmentioning
confidence: 99%